(3TQM YbGFO GdbGVj SQGL GdOjf GdGhTjs - (3GdfLGQj Gdjefj, Ndjd Hf GdYdGA, J (B632 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdehUha HChUGa GdceGd jbhd GdYHO aj HOA GdCeGdj dJhMjO HfXe cGddCdj jbhd ef Gdbhd hgh GdeJcde HcdGe UGOb Ch cGPH hGdYHO EfSGf jedcg ef dG jedc , hCQGO GdeDda Hg faSg s
(3BNQgG (B:s
(3ajg aGYdg jQLY Edi GdehUhd hdj LGQ heLQhQ eJYdb Hg hHGdNjQ eJYdb Hg bOe Ydjg ddGgJeGe hjeG fUH Ydi YGedg CjVG bO OYG dj hGdehUhd Y UdJg heJYdbG HgG aj eMd GdLQ dCLd GddGe hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2 / 1349s
(3cTa GdXfhf (B2 / 1349s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds